2010
DOI: 10.5016/1980-6574.2010v16n4p1024
|View full text |Cite
|
Sign up to set email alerts
|

Atividade física e funcionalidade do idoso

Abstract: Resumo: A adoção de um estilo de vida ativo proporciona diversos benefícios à saúde, uma vez que é considerado como um importante componente para a melhoria da qualidade de vida e da independência funcional do idoso. Porém, tão importante quanto investigar os benefícios biopsicossociais adquiridos pela prática da atividade física, é compreender os fatores associados que influenciam a sua adesão e manutenção. Sendo assim, a partir de uma revisão da literatura, o presente artigo tem como proposta discutir a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
97

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 15 publications
1
44
0
97
Order By: Relevance
“…Andrade et al 33 found a high prevalence of overweight and obesity, with 41.8% and 23.4%, respectively. The results of the present study found that most of the elderly persons surveyed (n=181; 57.9%) carried out physical activities and were considered as highly active or sufficiently active, which may have contributed to the relatively low frequency of overweight compared to other studies [3][4][5] .…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Andrade et al 33 found a high prevalence of overweight and obesity, with 41.8% and 23.4%, respectively. The results of the present study found that most of the elderly persons surveyed (n=181; 57.9%) carried out physical activities and were considered as highly active or sufficiently active, which may have contributed to the relatively low frequency of overweight compared to other studies [3][4][5] .…”
Section: Discussionmentioning
confidence: 54%
“…This reinforces the belief that physical inactivity can contribute to increased levels of depression in the elderly. The relationship between exercise, health, quality of life and aging is being increasingly discussed and analyzed scientifically by professionals from different areas [3][4][5][6]24,28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations